2012
DOI: 10.14419/ijans.v1i2.132
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Compliance of Standard Precautions among Student Nurses

Abstract: Student nurses are often exposed to various infections during their clinical education. Knowledge and compliance with standard precautions is essential to prevent hospital associated infections and protect patients as well as medical workers from exposure to infectious agents. This study assessed the knowledge and degree of compliance regarding standard precautions among student nurses in a government university in Samar, Philippines. A cross-sectional study was adopted for this investigation and data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
34
4
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 27 publications
19
34
4
5
Order By: Relevance
“…The present result was agreement with Labrague, et al, 2012 [31] they found in their study about knowledge and compliance with standards precautions that the young age of the studied sample had capability to gain knowledge and alter their behaviors. While Alwutaib et al, 2012 [32] they stated that older age is an important indicator to lesser knowledge levels.…”
Section: Discussionsupporting
confidence: 93%
“…The present result was agreement with Labrague, et al, 2012 [31] they found in their study about knowledge and compliance with standards precautions that the young age of the studied sample had capability to gain knowledge and alter their behaviors. While Alwutaib et al, 2012 [32] they stated that older age is an important indicator to lesser knowledge levels.…”
Section: Discussionsupporting
confidence: 93%
“…The knowledge level in these studies was (12.9, 10, and 37.7%), respectively. However, the level of knowledge in the current study is lower than what was found by Vaz et al [23] and Labrague et al [24], as it accounted for 90 and 89.7%, respectively. Such different levels of knowledge among nurses in these different studies might be due to the inadequacy of infection prevention and control training' education, as it was found that those nurses who attended in-service training courses achieved a high knowledge scores [25].…”
Section: Discussioncontrasting
confidence: 88%
“…Nurses in this study found to have a significant better self-reported compliance score than that achieved by doctors and assistant nurses which is in agreement with the results of Labrague et al 18 and Kim et al 19 who reported that student nurses have a high compliance of standard precautions. Similar data were found in another study with nursing staff.…”
supporting
confidence: 92%